Barriers to Investment in Utility-scale Variable Renewable Electricity (VRE) Projects - Hu, J.; Harmsen, R.; Crijns-Graus, W.; Worrell, E. (Elsevier Ltd, 2018)
To effectively mitigate climate change, variable renewable electricity (VRE) is expected to substitute a great share of current fossil-fired electricity generation. However, VRE investments can be obstructed by many barriers, endangering the amount of investments needed in order to be consistent with the Paris 2 °C target. To help policy-makers better understand and assess these barriers, an integrated framework was developed. It establishes a clear connection between barriers identified in literature and the investment decision-making process, based on the project life of VRE assets. Barriers in this framework are defined as factors hindering the realization of a positive final investment decision (FID), which can lead to investment withdrawal. Based on this research, we argue that addressing so-called “symptomatic” barriers alone is hardly effective when the “fundamental” barriers remain untouched. It also demonstrates that monetary and fiscal policies can have side-effects on VRE investments. We suggest that a comprehensive policy framework to support VRE should not be solely limited to the narrow context of climate and energy policy, and the electricity market. It should be incorporated in a broader context including monetary and fiscal policies. When re-designing these macroeconomic policies, their potential negative impacts on VRE investments should be considered.
Keywords: Variable renewable electricity; Barrier; Investment; Decision-making; Energy policy; SDG 7 - Affordable and Clean Energy; SDG 13 - Climate Action